LSD1+8a is an RNA biomarker of neuroendocrine prostate cancer - Anbarasu Kumaraswamy; Rahul Mannan; Olivia A. Swaim; Eva Rodansky; Xiao-Ming Wang; Aaron Udager; Rohit Mehra; Hui Li; Colm Morrissey; Eva Corey; Michael C. Haffner; Peter S. Nelson; et al. (Neoplasia: An International Journal for Oncology Research)
Background: Lysine-specific demethylase 1 (LSD1) is a histone demethylase and regulator of differentiation, including in cancer. A neuronal-specific isoform of LSD1—LSD1+8a—has been shown to play a key role in promoting neuronal differentiation in the developing brain. We previously determined that LSD1+8a transcripts were detected in an aggressive subtype of prostate cancer harboring a neuronal program—neuroendocrine prostate cancer (NEPC)—but not in prostate adenocarcinomas harboring a glandular program. However, the number of samples examined was limited. Methods: Using a large collection of prostate cancer patient cell lines and patient-derived xenografts (PDXs), we measured LSD1+8a using quantitative polymerase chain reaction (qPCR), RNA in situ hybridization (RNA-ISH), and protein detection methods. We then validated our findings using an independent cohort of patient tumor samples. Results: LSD1+8a mRNA expression was detected in every NEPC cell line and PDX examined by qPCR and RNA-ISH but in none of the prostate adenocarcinomas. We validated the RNA-ISH results in patient tumors, confirming that LSD1+8a was expressed in all NEPC tumors but in none of the adenocarcinomas. Finally, we generated a rabbit monoclonal antibody specific to LSD1+8a protein and confirmed its specificity using normal neuronal tissue samples. However, LSD1+8a protein was not detectable in NEPC tumors—likely due to the substantially lower levels of LSD1+8a mRNA in NEPC tumors vs. normal neuronal tissues. Conclusions: Measuring LSD1+8a mRNA is a sensitive and specific method for the diagnosis of NEPC, which is often challenging.